1997
DOI: 10.1126/science.276.5320.1851
|View full text |Cite
|
Sign up to set email alerts
|

Kaposi's Sarcoma-Associated Herpesvirus Infection of Bone Marrow Dendritic Cells from Multiple Myeloma Patients

Abstract: Kaposi's sarcoma-associated herpesvirus (KSHV) was found in the bone marrow dendritic cells of multiple myeloma patients but not in malignant plasma cells or bone marrow dendritic cells from normal individuals or patients with other malignancies. In addition the virus was detected in the bone marrow dendritic cells from two out of eight patients with monoclonal gammopathy of undetermined significance (MGUS), a precursor to myeloma. Viral interleukin-6, the human homolog of which is a growth factor for myeloma,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
219
4
3

Year Published

1998
1998
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 442 publications
(238 citation statements)
references
References 31 publications
12
219
4
3
Order By: Relevance
“…4 While a controversial increased incidence of multiple myeloma and other hematopoietic neoplasms in Classic Kaposi Sarcoma has been extensively reported in the literature, 14,16,18,[21][22][23][24][25][26][27][28][29] the suggested link between HHV-8 and multiple myeloma 30 supports an increase, such as noted in our study, in multiple myeloma in Kaposi Sarcoma patients. An increased incidence of other hematopoietic neoplasms was also observed in our cohort.…”
Section: Discussionsupporting
confidence: 79%
“…4 While a controversial increased incidence of multiple myeloma and other hematopoietic neoplasms in Classic Kaposi Sarcoma has been extensively reported in the literature, 14,16,18,[21][22][23][24][25][26][27][28][29] the suggested link between HHV-8 and multiple myeloma 30 supports an increase, such as noted in our study, in multiple myeloma in Kaposi Sarcoma patients. An increased incidence of other hematopoietic neoplasms was also observed in our cohort.…”
Section: Discussionsupporting
confidence: 79%
“…For example, Coussens et al (1999), using a mouse model of epithelial carcinogenesis, showed that inflammatory mast cells are involved in activating premalignant neovascularization in the skin and proposed a key functional role for these infiltrating cells during the premalignant stages of squamous carcinogenesis due to the release of specific pro-angiogenic proteases. In other studies, the production of growth factors (such as IL-6) by herpesvirusinfected dendritic cells and macrophages was shown to drive the initial proliferation of hematopoietic malignant cells and autoimmune deficiency syndromeassociated neoplasms (McGrath et al, 1995;Rettig et al, 1997). In both studies, herpesvirus sequences were detected only in the tumor-associated stromal cells (dendritic cells and macrophages) and not in the malignancies.…”
Section: Oncogenic Functions Of Stromal Cellsmentioning
confidence: 87%
“…The role of the EBV, HTLV, HIV, and KSHV in lymphomagenesis has been explored many times in several studies [14][15][16][17][18]. In the last years, the association between NHL and HCV has been studied extensively.…”
Section: Discussionmentioning
confidence: 99%